The Effectiveness of Teaching Materials for the Introductory Core Physics Course Based on the Use of PhET to Improve the Activity and Learning Outcomes of Physics Education Students - Susilawati; Aris Doyan; Lalu Muliyadi (Postgraduate, University of Mataram, 2023)
This study aims to examine the effectiveness of teaching materials for the introductory core physics course based on the use of PhET to improve the activity and learning outcomes of physics education students. The device was developed using a 4D model which includes define, design, develop and disseminate. The sample of this research was all 20 undergraduate students taking the core physics course. The data obtained in this study are in the form of activity data and student learning outcomes data. Student activity data obtained was then analyzed and adjusted to the value of activity criteria, while the increase in student learning out-comes was analyzed using the N-gain test. The results showed that the value of student activity ranged from 0.8 to 0.96 so that it was categorized as active and very active. The N-gain analysis shows that student learning outcomes have in-creased with a value of 0.73 to 0.77 and are in the high category. This means that the teaching materials for introductory core physics courses based on the use of PhET are effective in increasing the activities and learning outcomes of physics education students